Interactions Between Carbon Metabolism and Photosynthetic Electron Transport in a Chlamydomonas reinhardtii Mutant Without CO2 Fixation by RuBisCO - Saint-Sorny, Maureen; Brzezowski, Pawel; Arrivault, Stéphanie; Alric, Jean; Johnson, Xenie (Frontiers in Plant Science, 2022)
A Chlamydomonas reinhardtii RuBisCO-less mutant, ΔrbcL, was used to study carbohydrate metabolism without fixation of atmospheric carbon. The regulatory mechanism(s) that control linear electron flow, known as “photosynthetic control,” are amplified in ΔrbcL at the onset of illumination. With the aim to understand the metabolites that control this regulatory response, we have correlated the kinetics of primary carbon metabolites to chlorophyll fluorescence induction curves. We identify that ΔrbcL in the absence of acetate generates adenosine triphosphate (ATP) via photosynthetic electron transfer reactions. Also, metabolites of the Calvin Benson Bassham (CBB) cycle are responsive to the light. Indeed, ribulose 1,5-bisphosphate (RuBP), the last intermediate before carboxylation by Ribulose-1,5-bisphosphate carboxylase-oxygenase, accumulates significantly with time, and CBB cycle intermediates for RuBP regeneration, dihydroxyacetone phosphate (DHAP), pentose phosphates and ribose-5-phosphate (R5P) are rapidly accumulated in the first seconds of illumination, then consumed, showing that although the CBB is blocked, these enzymes are still transiently active. In opposition, in the presence of acetate, consumption of CBB cycle intermediates is strongly diminished, suggesting that the link between light and primary carbon metabolism is almost lost. Phosphorylated hexoses and starch accumulate significantly. We show that acetate uptake results in heterotrophic metabolism dominating phototrophic metabolism, with glyoxylate and tricarboxylic acid (TCA) cycle intermediates being the most highly represented metabolites, specifically succinate and malate. These findings allow us to hypothesize which metabolites and metabolic pathways are relevant to the upregulation of processes like cyclic electron flow that are implicated in photosynthetic control mechanisms.